ANALYSIS OF HOUSING OWNERS SATISFACTION LEVEL ON HOUSING CONSUMERS AT HOUSING FACULTY OF ENGINEERING UNHAS IN KAB. GOWA - Abd Karim Hadi Hadi; Ratna Musa Musa; Nurbaya (UNDERPASS Journal of Civil Engineering, Applied Sciences, and Technology, 2020)
Housing and settlements are one of the basic human needs. As written in the 1945 Constitution Article 28, that the house is one of the basic rights of the people and therefore every citizen has the right to live and get a good and healthy living environment. In addition, the house is also a basic human need in increasing the dignity, quality of life and livelihood, as well as as a reflection of oneself in an effort to improve the standard of living, as well as the formation of character, character and personality of the nation. Research Objectives To analyze expectations/needs, environmental quality, existence Facilities and infrastructure as well as Security Conditions. The method used is descriptive qualitative analysis using multiple regression equations. The population and sample are residents of the housing estate of the Hasanuddin University Faculty of Engineering in Gowa Regency. The results obtained from the five variables have an influence on the level of occupant satisfaction. And the variable that has a strong influence is on the expectation/needs variable, with a coefficient of 0.344 and the infrastructure variable of 0.288, so it is suggested that both variables can be followed up so that the level of satisfaction of the residents of the housing reaches the level of satisfaction.